2015
DOI: 10.4049/jimmunol.1402957
|View full text |Cite
|
Sign up to set email alerts
|

CD81 Controls Immunity to Listeria Infection through Rac-Dependent Inhibition of Proinflammatory Mediator Release and Activation of Cytotoxic T Cells

Abstract: Despite recent evidence on the involvement of CD81 in pathogen binding and Ag presentation by dendritic cells (DCs), the molecular mechanism of how CD81 regulates immunity during infection remains to be elucidated. To investigate the role of CD81 in the regulation of defense mechanisms against microbial infections, we have used the Listeria monocytogenes infection model to explore the impact of CD81 deficiency in the innate and adaptive immune response against this pathogenic bacteria. We show that CD81−/− mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 56 publications
1
17
0
Order By: Relevance
“…To ascertain the defective TLR-dependent inflammatory response in vivo due to the molecular association of MyD88-HDAC6, Hdac6 +/+ and Hdac6 -/- mice were intravenously injected with a lethal dose of Lm ( Fig 9F ) [ 44 ]. A protective effect against Lm -induced septic shock was observed from 3 to 10 days post-infection (dpi) ( Fig 9F ).…”
Section: Resultsmentioning
confidence: 99%
“…To ascertain the defective TLR-dependent inflammatory response in vivo due to the molecular association of MyD88-HDAC6, Hdac6 +/+ and Hdac6 -/- mice were intravenously injected with a lethal dose of Lm ( Fig 9F ) [ 44 ]. A protective effect against Lm -induced septic shock was observed from 3 to 10 days post-infection (dpi) ( Fig 9F ).…”
Section: Resultsmentioning
confidence: 99%
“…Wild type bone marrow cell suspensions were either cultured to obtain conventional DCs or both pDCs and cDCs as described 23, 24 . When indicated, OT-II CD4 T cells were cocultured with the corresponding subset of DCs (8:1T cell/DC ratio) in the presence or absence of chicken ovalbumin (OVA) 323–339 peptide.…”
Section: Methodsmentioning
confidence: 99%
“…Little is known regarding the contribution of CD81 to bacterial pathogenesis. Studies have shown that CD81 is required for the invasion (46) and infection (47) of Listeria monocytogenes. In the case of EPEC, CD81 does not seem to be required for bacterial colonization of cultured epithelial cells (not shown) or for F-actin clustering at infection sites (Fig.…”
Section: Discussionmentioning
confidence: 99%